Potential role of sacred grove of Lumbini in biodiversity conservation in Nepal - Bhattarai, Khem Raj; Baral, Sushim R (Banko Janakari, 2009)
This study was conducted in the sacred grove of Lumbini to elucidate its potential role in biodiversity conservation in Nepal. Lumbini Development Trust enumerated tree species of the grove. We have assessed taxonomic validity by identifying the species. A total of 65 tree species, 39 are indigenous to Nepal, were found in the grove. Most of the species were tropical/subtropical elements that are found to be distributed in Nepal from 100 to 2400m asl. Among total indigenous trees, 64 % trees have their distribution in the whole Nepal, whereas 19 %, 14 % and 3 % are limited to central, eastern, and both central and western part of Nepal respectively. The indigenous species found in the grove accounts for 11 % of total tree diversity of Nepal. Of these tree species, five are of threatened, vulnerable and endangered categories. The forest formation of the grove conforms to Dalbergia sisoo-Acacia catechu type's forest of Nepal. However, majority of the trees in the grove were produced by plantation so it has contributed to ex-situ conservation of trees, and hence this reflects the importance of sacred grove. Key words: conservation, distribution, indigenous trees, Lumbini, Sacred grove, sacred plants, tree species. doi: 10.3126/banko.v18i1.2163 Banko Janakari, Vol. 18, No. 1, 25-31